PENGARUH CORPORATE GOVERNANCE TERHADAP VOLUNTARY DISCLOSURE DAN BIAYA HUTANG - YUNITA, NANCY (Universitas Katolik Widya Mandala Surabaya, 2012)
This research aims to determine direct influence corporate governance towards the cost of debt and the indirect influences corporate governance towards the cost of the debt with the voluntary disclosure as the moderate variable. This is the entire population research manufacturing companies listed on the Indonesia stock exchange with a period of observation in 2008-2010. Sampling using a purposive sampling based on predetermined criteria. Twenty-six companies are being sampled. Corporate governance diproksikan with managerial ownership, institutional ownership, Commissioner of the independent, and the quality of audits. The methods used in the study is path analysis with multiple regression.The results of this research suggest that institutional ownership of significant positive impact on the cost of debt and the negative impact of significant quality audit of the cost of debt, whereas managerial ownership, Commissioner of the independent and voluntary disclosure does not affect the cost of debt. And overall corporate governance does not affect voluntary disclosure.